1975
DOI: 10.1037/0096-1523.1.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The use of structural diagnostics in recognition.

Abstract: The suggestion of Krueger (1973) and others that wholistic processes underlie certain perceptual judgments is taken up in this paper. It is argued that properties such as bilateral symmetry can have a "diagnostic" significance for visual matching tasks. Diagnosticity means that if the property is present the appropriate response to a stimulus could theoretically 'be determined without any other analysis of the stimulus. Experiments 1 and 2 indicate that symmetry is exploited as a diagnostic property for the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 6 publications
3
43
0
Order By: Relevance
“…This is supportive of symmetry as a "diagnostic" allowing fast "same" responses (Fox, 1975),since a diagnostic would be expected to become more beneficial as similarity increased. In effect, the presence of similar "different" pairs should make subjects cautious and thus slow in making same responses; symmetry can then exert a larger diagnostic effect than otherwise.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is supportive of symmetry as a "diagnostic" allowing fast "same" responses (Fox, 1975),since a diagnostic would be expected to become more beneficial as similarity increased. In effect, the presence of similar "different" pairs should make subjects cautious and thus slow in making same responses; symmetry can then exert a larger diagnostic effect than otherwise.…”
Section: Discussionmentioning
confidence: 87%
“…If the disparity varies with visual similarity (Bindra et al, 1968), this would suggest either a two-process letter-comparison model or a single-process model combined with a criterion shift. Third, the use of symmetry as a "structural diagnostic" is investigated, since it has been found that symmetry can speed "same" responses (Fox, 1975;Richards, 1978), an observation unaccounted for in any of the preceding models. If found, such an effect would implicate a two-process comparison model, since symmetry should not in itself affect a difference count.…”
mentioning
confidence: 99%
“…As a result, the comparison process could be affected by two factors. One factor is symmetry of the whole display (Fox, 1975). If global symmetry is salient in some way, it could facilitate "same"/"different" judgments on the global dimension (see also Navon, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been claimed that symmetry about a vertical axis is more salient than symmetry about any other axis (Mach 1959;Rock & Leaman 1963;Goldmeier 1972;Rock 1973;Corballis & Roldan 1975;Fox 1975;Barlow & Reeves 1979;Fisher & Fracasso 1987). Explicitly, there are data to indicate a hierarchy in ease of detection so that symmetry in a vertical plane is easiest to detect, followed by horizontal symmetry and then diagonal symmetry (Palmer & Hemenway 1978;Barlow & Reeves 1979;Royer 1981).…”
Section: (A) Orientation Of the Axis Of Symmetrymentioning
confidence: 99%